2022
DOI: 10.1093/jxb/erac107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of early phenology in lentil identifies distinct loci controlling component traits

Abstract: Modern-day domesticated lentil germplasm is generally considered to form three broad adaptation groups: Mediterranean, South Asian and northern temperate, which correspond to the major global production environments. Reproductive phenology plays a key role in lentil adaptation to this diverse ecogeographic variation. Here, we dissect the characteristic earliness of the pilosae ecotype, suited to the typically short cropping season of South Asian environments. We identified two loci, DTF6a and DTF6b, at which d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Extensive research revealed that the flowering-related genes are largely conserved between Arabidopsis and legumes [ 42 , 44 , 45 , 49 , 53 , 54 , 55 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. However, the legumes generally lack any FLC orthologs, except for soybean, a vernalization-independent species, which retained one FLC copy in its paleopolyploid genome [ 42 , 98 , 99 ].…”
Section: The Mechanism Of Cold–induced Flowering In Arabido...mentioning
confidence: 99%
See 4 more Smart Citations
“…Extensive research revealed that the flowering-related genes are largely conserved between Arabidopsis and legumes [ 42 , 44 , 45 , 49 , 53 , 54 , 55 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. However, the legumes generally lack any FLC orthologs, except for soybean, a vernalization-independent species, which retained one FLC copy in its paleopolyploid genome [ 42 , 98 , 99 ].…”
Section: The Mechanism Of Cold–induced Flowering In Arabido...mentioning
confidence: 99%
“…Legumes have three subclades of FT genes ( FTa, FTb and FTc ) with five Arabidopsis FT orthologs detected in pea Pisum sativum , and six orthologs in Medicago trancatula and Lens culinaris ( Table 1 ) [ 44 , 45 , 53 , 55 , 56 , 100 ]. Unlike pea and Medicago , chickpea Cicer arietinum has a single FTb gene, resulting in a family of five genes ( Table 1 ) [ 54 ].…”
Section: Ft Genes In Legumesmentioning
confidence: 99%
See 3 more Smart Citations